Large-Area Fabrication of Structurally Colored and Humidity Sensitive Composite Nanofilm via Ultrasonic Spray-Coating - Sijun Li (MDPI AG, 2021)
Intelligent structural colors have received extensive attention in recent years due to their diverse applications. However, the large-area, uniform, and cost-effective fabrication of ultra-thin structural color films is still challenging. Here, for the first time, we design and employ an ultrasonic spray-coating technique with non-toxic, green nano-silica and polyvinylpyrrolidone as raw materials, to prepare structural color films on silicon wafers. Due to the addition of polyvinylpyrrolidone, the coffee-ring effect during droplet drying is suppressed and uniform composite films are formed. We further perform a detailed study of the influence of various processing parameters including silica/polyvinylpyrrolidone concentration, substrate temperature, nozzle-to-substrate distance, and number of spray-passes on film roughness and thickness. By increasing the number of spray-passes from 10 to 30, the film thickness from 120 to 340 nm is modulated, resulting in different colors, and large-area and uniform colors on commercial round silicon wafers with 15 cm diameter are achieved. The silica/polyvinylpyrrolidone composite films show strong hydrophilicity and are sensitive to humidity changes, leading to quickly tunable and reversible structural colors. Quartz crystal microbalance with dissipation demonstrates water vapor adsorption and condensation on the nanofilm when increasing environmental humidity. Thereby, ultrasonic spray-coating as a novel film fabrication technique provides a feasible scheme for large-area preparation of intelligent structural colors.